2019
DOI: 10.2196/14050
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of the Perceived Transparency of Privacy Policies and Trust in Providers for Building Trust in Health Information Exchange: Empirical Study

Abstract: BackgroundIn the context of exchange technologies, such as health information exchange (HIE), existing technology acceptance theories should be expanded to consider not only the cognitive beliefs resulting in adoption behavior but also the affect provoked by the sharing nature of the technology.ObjectiveWe aimed to study HIE adoption using a trust-centered model. Based on the Theory of Reasoned Action, the technology adoption literature, and the trust transfer mechanism, we theoretically explained and empirica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 91 publications
(125 reference statements)
3
34
2
Order By: Relevance
“…One way to interpret this is that one learns through previous experience what to expect (correct or not) about risks and consequences if things go bad. This is not to deny that trust may also be influenced by other factors, for instance negative reports in traditional and social media, but how such news are perceived may be strongly influenced by what level of trust one already has [ 23 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…One way to interpret this is that one learns through previous experience what to expect (correct or not) about risks and consequences if things go bad. This is not to deny that trust may also be influenced by other factors, for instance negative reports in traditional and social media, but how such news are perceived may be strongly influenced by what level of trust one already has [ 23 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that a privacy policy can improve user trust and loyalty in health care providers, thus influencing health information exchange behaviors in users [27]. In the interactive professional health care knowledge sharing process of an OHC, patients may increase their trust in doctors when they are protected by doctors' privacy protection settings, thus feeling encouraged to share more personal health care information during communication [28].…”
Section: The Enhancing Power Of Privacy Protection On Interactive Promentioning
confidence: 99%
“…Increased access to data for secondary use is complex and continues to attract strong debate within the health and scientific communities as well as the general public. While researchers are now being encouraged to increase data accessibility for secondary research [ 6 , 7 ], a range of stakeholder-perceived barriers and concerns remain, including issues such as trust, transparency, and privacy [ 8 , 9 ]. Despite the impact of these issues on willingness to share data, there is a lack of synthesis of stakeholder views to guide policy and practice.…”
Section: Introductionmentioning
confidence: 99%